A semi-synthetic flavonoid from Bauhinia pulchella stem attenuates inflammatory osteolysis in periodontitis in rats: Impact on cytokine levels, oxidative stress, and RANK/RANKL/OPG pathway. (September 2020) - Pinto, Isabela R.; Chaves, Hellíada V.; Freire, Jordânia M.O.; de Sousa, Luzia Herminia T.; Monteiro, Dina A.M.; Costa, José Jackson do N.; Pereira, Karuza M.A.; Santiago, Gilvandete Maria P.; de Sousa, Leôncio M.; da Silva, Marcos Reinaldo; Monteiro, Aurélio de O.; Montenegro, Raquel de C.; et al.
Highlights: Effect of a semi-synthetic flavonoid from B. pulchella on periodontitis in rats. Abstract: Objectives: Many species of the Bauhinia genus have been widely used in folk medicine as analgesic, anti-inflammatory and antioxidant agents. (-)-Fisetinidol palmitate is a semi-syntetic flavonoid obtained from the ethanolic extract of the stem of Bauhinia pulchella. This study aimed to evaluate the antiresorptive effect of the semi-syntetic (-)-fisetinidol palmitate in ligature-induced periodontitis in rats. Also, it evaluated the mechanism of action of (-)-fisetinidol palmitate and its toxicity. Design: Periodontitis was induced via a nylon thread ligature (3.0) around the second upper left molars. Rats were treated (oral gavage) once a day for 11 days with (-)-fisetinidol palmitate (0.01 or 0.1 mg/kg) or saline vehicle. Results: (-)-Fisetinidol palmitate (0.1 mg/kg) reduced alveolar bone loss, increased bone alkaline phosphatase (BALP), superoxide dismutase (SOD), and catalase (CAT) activity; also, it decreased IL1-β, IL-8/CINC-1, nitrite/nitrate levels and myeloperoxidase activity. (-)-Fisetinidol palmitate reduced the mRNA levels of IL1-β, IL-6, RANK, and RANK-L, while it increased the OPG ones. No statistical differences (P > 0.05) were observed in the transaminases (ALT, AST) and Total Alkaline Phosphatase (TALP) levels among groups. (-)- Conclusions: Fisetinidol palmitate did not result in any signs of toxicity and had anti-resorptive effects in a pre-clinical trial of periodontitis, showing antioxidant activity with the involvement of the RANK/RANKL/OPG pathway.